The Role of Stok Bina Guna Students in Socializing the Physical Education Study Program for Progress Sport in Medan City 2025 - Josep Perlindungan Halawa; Vincentius Gokmaruli Sidabutar; Dirly Laurensius Perangin Angin (CV. INSPIRETECH GLOBAL INSIGHT, 2026)
Purpose of the study: Activity devotion public This aim for increase understanding Medan City community about the role of the Physical Education Study Program in coaching exercise, improve interest generation young to education physical and sports, as well as build synergy between college tall sport with sports stakeholders in Medan City to support progress performance sport area. Materials and methods: Activity implemented through approach participatory with involving students of the Physical Education, Health and Recreation Study Program, STOK Bina Guna as agent socialization. The method used covering socialization interactive in schools middle, clinic sports, coaching workshops coach young, and collaboration with KONI Medan City. Activities implemented during sixmonth from March to August 2025, with involving 15 schools medium and 250 participants from circles students, teachers, and coaches young. Results: Activity socialization succeed increase understanding participant about importance education physical by 78% based on pre-test and post-test results. A total of 142 students state interest for continue education to field sports, and intertwined cooperation with 8 clubs sport local for coaching programs sustainable. STOK Bina Guna students also succeeded identified 67 seeds athlete recommended potential for coaching continued. Conclusions: STOK Bina Guna students have role strategic in socialization of the Physical Education Study Program and contributing significant to progress sports in Medan City. Activities This prove that collaboration between college tall sports, schools, and organizations sport local can become an effective model for increase quality coaching sport Regional. Program sustainability is needed with regular support from local governments and relevant stakeholders.